2018
DOI: 10.3390/ijms19010247
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Sphingolipid World in Inflammation Specific for Lysosomal Storage Diseases and Skin Disorders

Abstract: Research in recent years has shown that sphingolipids are essential signalling molecules for the proper biological and structural functioning of cells. Long-term studies on the metabolism of sphingolipids have provided evidence for their role in the pathogenesis of a number of diseases. As many inflammatory diseases, such as lysosomal storage disorders and some dermatologic diseases, including psoriasis, atopic dermatitis and ichthyoses, are associated with the altered composition and metabolism of sphingolipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 201 publications
(235 reference statements)
1
19
0
Order By: Relevance
“…Another theory of LysoGb3 accumulation in neuronopathic forms of MPSs may be the relationship between lactosylceramide (LacCer) and globotriaosylceramide (Gb3) ( Figure 5). There is evidence that LacCer accumulates in MPS II and III [16,17], and it is the main core of most gangliosides [18]. It is also reported that LacCer is one of the main accumulated components in the brain samples of patients with neurological forms of MPSs; however, a significant increase of Gb3 was not fixed [19].…”
Section: Discussionmentioning
confidence: 99%
“…Another theory of LysoGb3 accumulation in neuronopathic forms of MPSs may be the relationship between lactosylceramide (LacCer) and globotriaosylceramide (Gb3) ( Figure 5). There is evidence that LacCer accumulates in MPS II and III [16,17], and it is the main core of most gangliosides [18]. It is also reported that LacCer is one of the main accumulated components in the brain samples of patients with neurological forms of MPSs; however, a significant increase of Gb3 was not fixed [19].…”
Section: Discussionmentioning
confidence: 99%
“…15,16 Simultaneous disturbances in ceramide levels in skin lesions and blood of affected patients was detected in only one study but this was only observed in severe and not mild or moderate psoriasis. 17 Other recent studies detected a decrease in serum plasma levels of ceramide in patients compared to healthy controls. On the contrary, one report detected increased levels of ceramide in both lesional skin as well as in blood of patients compared to controls.…”
Section: Discussionmentioning
confidence: 92%
“…Cantuti et al reported abnormal expression of caspase 3 in presynaptic terminals of the twitcher mouse, which underlines the possibility that exacerbated degradation of synaptic components by caspase activities impact on nerve transmission (Cantuti-Castelvetri et al, 2015 ). Considering that inflammation of the nerve tissue is an integral part of the cellular response in most neurological LSDs (Moskot et al, 2018 ), the activation of microglia, inflammation, and cell death pathways are likely to influence synaptic function in these diseases and contribute to some of the neurobehavioral manifestations observed in patients.…”
Section: Inflammation As a Contributor To Synaptic Failure In Lsdsmentioning
confidence: 99%